Interface-mediated hygroelectric generator with an output voltage approaching 1.5 volts - Yaxin Huang (Nature Portfolio, 2018)
Hygroelectric generators comprised of electrodes and a hygroscopic material with a chemical-gradient structure can produce electricity by absorbing water vapor. Here, the authors achieve a high output voltage by employing hygroscopic heterogeneous graphene oxide and materials with Schottky junctions.